2022
DOI: 10.1021/acs.jafc.1c07726
|View full text |Cite
|
Sign up to set email alerts
|

Pyocyanin Modulates Gastrointestinal Transformation and Microbiota

Abstract: Phenazines are ubiquitously produced by Pseudomonas spp. in the environment and are widely used in agriculture and clinical therapies, making their accumulation through the food chain cause potential risks to human health. Here, we utilized pyocyanin (PYO) as a representative to study the effects of phenazines on digestive tracts. Pharmacokinetic analysis showed that PYO exhibited low systemic exposure, slow elimination, and low accumulation in both rat and pig models. PYO was subsequently found to induce inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Phenazine and angucycline related compound genes can be plasmid linked ( Novakova et al, 2013 ; Rui et al, 2012 ) so co-occurrence with metal resistance genes is possible, however generally not reported in the intestinal tract. However, the phenazine compound pyocyanin, when introduced into the intestinal tract, does modulate both the intestinal flora and metabolism ( Peng et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Phenazine and angucycline related compound genes can be plasmid linked ( Novakova et al, 2013 ; Rui et al, 2012 ) so co-occurrence with metal resistance genes is possible, however generally not reported in the intestinal tract. However, the phenazine compound pyocyanin, when introduced into the intestinal tract, does modulate both the intestinal flora and metabolism ( Peng et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Li et al (2018) also reported that PYO is well-tolerated by probiotic microorganisms (Lactobacillus spp.). However, considering an opposing conclusion made by Peng et al (2022) who indicated that PYO may be detrimental to the function of intestinal microbiota, it appears that further experimental investigations still have to be carried out. Regarding humans, the current data cannot exclude that ingesting PYO will cause adverse effects.…”
Section: Why Is Pyocyanin Production Worth Controlling?mentioning
confidence: 99%
“…However, higher concentrations resulted in opposite observations. Peng et al (2022) analysed the influence of PYO on mice and pig digestive tracts. The authors proved that PYO exposure led to dysbiosis of microbiota and damage to the mucus layer.…”
Section: Why Is Pyocyanin Production Worth Controlling?mentioning
confidence: 99%
“…3,4 Due to the broad-spectrum antimicrobial activity against various bacterial and fungal pathogens, several phenazines, such as phenazine-1-carboxylic acid and phenazine 5-oxide, have been approved as pesticides in agricultural crops. 5,6 Phenazines have low molecular weight and zwitterionic properties, allowing them to easily penetrate cell membranes and cross through the blood–brain barrier, resulting in cell damage. 7 Moreover, the redox-active tricyclic zwitterion forms reactive oxygen species (ROS), a process which can influence the cardiovascular, respiratory, urological, and central nervous systems.…”
Section: Introductionmentioning
confidence: 99%